2005
DOI: 10.1111/j.1471-4159.2005.03380.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the cannabinoid CB2 receptor in microglial cells in response to inflammatory stimuli

Abstract: The cannabinoid system is known to be important in neuronal regulation, but is also capable of modulating immune function. Although the CNS resident microglial cells have been shown to express the CB 2 subtype of cannabinoid receptor during non-immune-mediated pathological conditions, little is known about the expression of the cannabinoid system during immune-mediated CNS pathology. To examine this question, we measured CB 2 receptor mRNA expression in the CNS of mice with experimental autoimmune encephalomye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
325
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 433 publications
(353 citation statements)
references
References 59 publications
(92 reference statements)
25
325
1
2
Order By: Relevance
“…In addition, Maresz et al (2005) have shown previously that CB 2 expression is upregulated in microglial cells in autoimmune-induced inflammation of the CNS in mice. Our results show that the distribution of these CB 2 -positive cells correlates with that of MHC-II-positive cells, whose localization and abundance are used as defining markers of plaque subtype (Trapp et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Maresz et al (2005) have shown previously that CB 2 expression is upregulated in microglial cells in autoimmune-induced inflammation of the CNS in mice. Our results show that the distribution of these CB 2 -positive cells correlates with that of MHC-II-positive cells, whose localization and abundance are used as defining markers of plaque subtype (Trapp et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of CB2 expression in microglia has since been repeated in subsequent studies, and may have important implications for drugs targeting CB2 at various stages of microglial activation (see section 4). Most recently, Maresz et al [35] have demonstrated that the combination of IFN-and granulocyte mononuclear colony stimulating factor (GM-CSF) induces even higher levels of microglial CB2.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…In the central nervous system (CNS), MGL hydrolyzes 2-AG to arachidonic and glycerol, which plays an essential role in the regulation of endocannabinoid signaling (Scheme 1) [7]. An overexpression of MGL in the CNS has been associated with various neurological diseases because immoderate hydrolysis of 2-AG impairs the physiological roles of CB 1 and CB 2 [8,9]. These findings have motivated the development of MGL inhibitors, including a non-covalent inhibitor URB602 with low potency and selectivity for MGL [10] and irreversible covalent inhibitors such as 4-nitrophenyl-carbamate JZL184 [11], N-arachidonylmaleimide [12], and SAR629 [13].…”
Section: Introductionmentioning
confidence: 99%